Identifying the Components of Cognitive Decline from the Perspective of Older Adults: A Qualitative Study - Barghi Irani , Maryam; Alipour, Ahmad; Barghi irani , Ziba; Qodsi, Parvaneh (KMAN Counseling & Psychology Nexus, 2026)
The aim of this study was to identify the components of cognitive decline from the perspective of older adults: a qualitative study. In terms of purpose, this research was applied, and in terms of methodology, it was qualitative. The statistical population of the study included all older adults in Districts 1 and 3 of Tehran, among whom 17 older adults were selected as the sample through theoretical sampling. The data collection instrument was a semi-structured interview. The qualitative analysis of the interviews resulted in 20 initial codes. Based on these codes, 9 subthemes were identified, and ultimately, 9 main themes were considered as the components of cognitive decline, which formed the basis for designing the cognitive decline questionnaire in this study. For each component, 10 items were proposed. Based on the opinions of 9 experts and university professors, the total content validity score was obtained as 0.78; therefore, the designed questionnaire had appropriate validity. The reliability of the questionnaire was obtained as 85% through two stages of coding with a one-month interval.